WORKSHOP PENULISAN LAPORAN HASIL PENELITIAN BAGI GURU SMK NEGERI 1 JETIS MOJOKERTO - Sri Rahayu; Liknin Nugraheni; Restu Ria wantika; Eko Sugandi (STKIP PGRI Sidoarjo, 2021)
Professional development of teachers should be developed through skills in research and writing scientific articles. The majority of teachers have difficulty writing research results that meet standards. Thus, this service activity was carried out with the aim of strengthening the teachers of SMK Negeri 1 Jetis Mojokerto in writing reports on the results of the research that had been carried out. The service is implemented in three stages, namely: (1) the planning phase; (2) training stage; (3) assessment of the sustainability of the program. Based on the community service activities carried out, he managed to open the horizons of the teachers of SMK Negeri 1 Jetis Mojokerto, especially with regard to the writing of research reports. According to the results of the program evaluation, the majority of teachers up to 100% were very satisfied with the workshop activities carried out. These activities provide an overview of the procedures and procedures for writing good and correct research reports. Thus, the participants were very enthusiastic to participate in the activities presented during the workshop on research report writing. Keywords: Writing of reports, research results, Vocational High School teachers